GEOGRAPHIC DISTRIBUTION AND HOSTS OF ANCYLOSTOMA PLURIDENTATUM (ALESSANDRINI, 1905) (NEMATODA, ANCYLOSTOMATIDAE) IN THE AMERICAS - Noronha, Dely (2021)
To date there were no reports of the history of Ancylostoma pluridentatum that was described in Italy, on the basis of Brazilian specimens in 1905. The only two further autochthonous references of the species occurred in 1910 and 2008, respectively, with no previous historical data during those 98 years in which the species was ignored in Brazil; in the present note, the occurrence of A. pluridentatum in the Americas is briefly accounted, on what concerns geographical distribution and hosts. In South America, A. pluridentatum is referred in the southeast (Atlantic Forest) and north (Amazon rain forest) regions of Brazil, in Argentina (Formosa Province) and in Colombia (Choco, Nariño); in Central America is cited in Panama (Achiote, Colon) and in North America in north, southern and south regions of Florida.